Prevenção De Ansiedade E Promoção De Habilidades Socioemocionais Em Pré-Escolares - Rivero, Lina Maria Herrera Nunez [UNIFESP] (2018)
Increasingly, Anxious Symptoms Have Been Alerted To Children Under 5 Years Of Age, So Early Identification Of Psychological Distress And The Difficulties These Children Present Is Essential, Since If Left Untreated They Can Worsen Over The Years , Making It Necessary To Invest In Programs That Can Help Preschool Children To Reduce Risk Factors And Develop Protective Factors For Mental Disorders, It Is Known That Early Intervention Can Reduce The Risk Of Future Disease Or The Severity Of The Own Disorder Anxiety. Objectives: To Evaluate The Effects Of The Funfriends Protocol On The Symptoms Of Anxiety, Internalizing Problems And Prosocial Behavior In Children Aged 4 To 5 Years. Method: A Total Of 43 Children (Experimental Group - Ge, N = 21, Control Group - Gc; N = 22) Participated In A Public Nursery School In The City Of São Paulo. The Behaviors Were Evaluated In Three Different Periods Through Standardized Questionnaires (Sbp, Cbcl, Sdq, Psa) On The Behavioral Profile Of The Children. Results: The Data Indi